Nitric Oxide in the Pathogenesis and Treatment of Tuberculosis - Jamaati, Hamidreza; Mortaz, Esmaeil; Pajouhi, Zeinab; Folkerts, Gert; Movassaghi, Mehrnaz; Moloudizargari, Milad; Adcock, Ian M.; Garssen, Johan (Frontiers in Microbiology, 2017)
Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis (TB), is globally known as one of the most important human pathogens. Mtb is estimated to infect nearly one third of the world's population with many subjects having a latent infection. Thus, from an estimated 2 billion people infected with Mtb, less than 10% may develop symptomatic TB. This indicates that the host immune system may constrain pathogen replication in most infected individuals. On entering the lungs of the host, Mtb initially encounters resident alveolar macrophages which can engulf and subsequently eliminate intracellular microbes via a plethora of bactericidal mechanisms including the generation of free radicals such as reactive oxygen and nitrogen species. Nitric oxide (NO), a key anti-mycobacterial molecule, is detected in the exhaled breath of patients infected with Mtb. Recent knowledge regarding the regulatory role of NO in airway function and Mtb proliferation paves the way of exploiting the beneficial effects of this molecule for the treatment of airway diseases. Here, we discuss the importance of NO in the pathogenesis of TB, the diagnostic use of exhaled and urinary NO in Mtb infection and the potential of NO-based treatments.